An analytical study of the offensive attack to the Iraqi national team players participating in the 2012 West Asian Championships and the Arabian Gulf 2013 for Soccer - Kadhim, Najy; Sami, Fares (Journal of Physical Education, 2015)
Researchers used a descriptive approach and the sample of research was the Matches of Iraqi team participating in the both champions. From 9 games just only 7 Matches was analyzed. Equipment and various tools and different setups were used. The researchers introduced a single game on the computer screen in order to calculate the number of successful and unsuccessful times for each attack. Analyze were began on Sunday 6/23/2013 and ended on Tuesday 07/02/2013, took Analysis (10) days through analyzing one Match every day and in the next day found the re-analysis for the same Match in order to reach the most accurate results in the analysis process